Emerging roles of selenium on metabolism and type 2 diabetes - Zhao, Jiuxiang; Zou, Hong; Huo, Yanling; Wei, Xiaoyi; Li, Yu (Frontiers in Nutrition, 2022)
Selenium is recognized as an essential element for human health and enters human body mainly via diet. Selenium is a key constituent in selenoproteins, which exert essential biological functions, including antioxidant and anti-inflammatory effects. Several selenoproteins including glutathione peroxidases, selenoprotein P and selenoprotein S are known to play roles in the regulation of type 2 diabetes. Although there is a close association between certain selenoproteins with glucose metabolism or insulin resistance, the relationship between selenium and type 2 diabetes is complex and remains uncertain. Here we review recent advances in the field with an emphasis on roles of selenium on metabolism and type 2 diabetes. Understanding the association between selenium and type 2 diabetes is important for developing clinical practice guidelines, establishing and implementing effective public health policies, and ultimately combating relative health issues.